Von Hayek's theory of cultural evolution in the light of a simplified model of Kaufmann's general biological evolutionary theory - Stephan Wolf (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2010)
In this paper, Hayek's theory of cultural evolution is compared to a simplified general macro-model of evolution based on Kaufmann (1993). It is shown how under certain condi-tions evolutionary lock-ins can occur, what consequences this has for the assessment of evolutionary results, and how lock-ins may be overcome. This last issue leads to three in-teresting results: the interdependency of orders matters, a purely macro-based model of evolution neglects population dynamics, and deliberately designed changes can be an important driving force for evolutionary development. The conclusion is that rule design combined with evolutionary selection may explain how group selection occurs, a point in-sufficiently addressed in Hayek's theory.
Keywords: 330